Digital Devices Use and Chinese-Canadian First Graders’ Early English Literacy Development: A Mixed-Methods Study - Guofang Li; Fubiao Zhen; Ziwen Mei (Education Sciences)
This mixed-methods study investigates the impact of digital devices use at home on early English literacy development among 121 Chinese-Canadian first graders, as well as their parents’ perspectives on the families’ purposes and practices of digital devices use for English literacy, highlighting bilingual children’s experiences with multiple digital devices. To understand the relationships between the children’s digital practices and early English literacy development, we collected quantitative data on children’s English literacy skills—including reading comprehension, decoding, and receptive vocabulary—alongside frequency data on digital devices use including those on computer use and television viewing. Parents of 66 children participated in interviews, providing context-specific insights into devices use purposes and language learning practices. Data analysis included descriptive statistics and independent samples t-tests to examine group differences. Hierarchical linear regression explored associations between digital devices use and early English literacy outcomes, while thematic analysis identified patterns from parental interviews. Results indicate a positive association between controlled television exposure and receptive vocabulary. However, no significant relationship was observed between television or computer use and decoding or reading comprehension. Findings emphasize the multifaceted but limited role of digital devices, with parents struggling to balance educational benefits and long-term concerns.